2017
DOI: 10.1016/j.celrep.2017.06.081
|View full text |Cite
|
Sign up to set email alerts
|

The Type VI Secretion System Engages a Redox-Regulated Dual-Functional Heme Transporter for Zinc Acquisition

Abstract: The type VI secretion system was recently reported to be involved in zinc acquisition, but the underlying mechanism remains unclear. Here, we report that Burkholderia thailandensis T6SS4 is involved in zinc acquisition via secretion of a zinc-scavenging protein, TseZ, that interacts with the outer membrane heme transporter HmuR. We find that HmuR is a redox-regulated dual-functional transporter that transports heme iron under normal conditions but zinc upon sensing extracellular oxidative stress, triggered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 32 publications
0
94
0
3
Order By: Relevance
“…Evidence accumulated in recent years has demonstrated that G. mellonella larvae can be used as an attractive alternative model to identify the virulence of various pathogens (42,(47)(48)(49)(50). In this study, we investigated the extent to which the virulence factors required for pathogenesis in both ducklings and G. mellonella larvae overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence accumulated in recent years has demonstrated that G. mellonella larvae can be used as an attractive alternative model to identify the virulence of various pathogens (42,(47)(48)(49)(50). In this study, we investigated the extent to which the virulence factors required for pathogenesis in both ducklings and G. mellonella larvae overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recently has been shown that in response to oxidative stress, T6SS from Yersinia pseudotuberculosis and Burkholderia thailandensis secrete effectors involved in ion uptake. The ion import is further mediated by ABC and/or TonB-family proteins [35][36][37].…”
Section: Genomic Context Of T6ss Genesmentioning
confidence: 99%
“…in Burkholderia thailandenss was found to secrete a proteinaceous zincophore, which interacts with the outer membrane heme transporter to import zinc under oxidative stress [30]. Given that the transcriptional changes of other zinc importers, such as znu and zip, were not observed in the current study, we postulated that T6SS also plays an important role in zinc transport in P. fluorescens, the downregulation of which reduced the transport of zinc across the outer membrane.…”
Section: Strainmentioning
confidence: 64%